2006
DOI: 10.3341/kjo.2006.20.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Chamber Intraocular Lens Implantation in Pediatric Cataract with Microcornea and/or Microphthalmos

Abstract: PurposeTo report the results of secondary posterior chamber intraocular lens (PC-IOL) implantation in pediatric cataract eyes with microcornea and/or microphthalmos.MethodsRetrospective studies were conducted by reviewing the charts of 26 eyes of 15 patients with secondary PC-IOL implantations for microcornea and/or microphthalmos associated with cataract in children between 1999 and 2002. The corneal diameter was 9.5 mm or less at the time of secondary PC-IOL implantation. Preoperative examinations were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…18 There are few reports of cataract surgery in eyes with microcornea, and there are no studies of the use of transscleral-fixated PC IOLs in eyes with zonular dialysis. 5,6,[19][20][21][22][23][24][25][26][27][28] Gimbel et al 19 reported inserting PC IOLs in bilateral microcorneas with corneal diameters of 9.43 mm and 9.61 mm and ALs of 19.29 mm and 19.23 mm to obtain a postoperative bilateral CDVA of 20/20. Dahan 20 reported that with unilateral congenital and developmental cataracts, a pediatric PC IOL can be inserted in the capsular bag unless the corneal diameter is less than 9.5 mm.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…18 There are few reports of cataract surgery in eyes with microcornea, and there are no studies of the use of transscleral-fixated PC IOLs in eyes with zonular dialysis. 5,6,[19][20][21][22][23][24][25][26][27][28] Gimbel et al 19 reported inserting PC IOLs in bilateral microcorneas with corneal diameters of 9.43 mm and 9.61 mm and ALs of 19.29 mm and 19.23 mm to obtain a postoperative bilateral CDVA of 20/20. Dahan 20 reported that with unilateral congenital and developmental cataracts, a pediatric PC IOL can be inserted in the capsular bag unless the corneal diameter is less than 9.5 mm.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4] The size of the surgical incision, mode of lens removal, type of intraocular lens (IOL) used, and method used to determine IOL power are modified for eyes with microcornea. 5,6 Microcornea can present alone or with syndromes, eg, microphthalmia (often) and macrophthalmia (rarely). [5][6][7] It might also be associated with developmental deformity in ciliary zonular fibers, which can cause lens subluxation and intraoperative zonular dialysis during cataract extraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 9 of the 12 (75%) bilateral cases used aphakic glasses. There have been reports of primary and secondary posterior chamber IOL implantation in eyes with microcornea [23][24][25][26] with relatively good visual outcomes. We implanted secondary IOLs in both eyes of two patients 3 years after the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,1820 In this cross-sectional study, we first qualitatively classified the capsular outcomes in aphakic eyes 12 months after pediatric cataract surgery into 3 types based on the degree and range of PCOO. We discovered that the types (scores) of capsular outcomes were negatively correlated with intraoperative anterior capsulorhexis size but had no significant correlation with intraoperative posterior capsulorhexis size.…”
Section: Discussionmentioning
confidence: 99%